MEDB-07. Long-term medical and functional outcomes of medulloblastoma survivors: a population-based, matched cohort study. (3rd June 2022) - Coltin, Hallie; Pequeno, Priscila; Liu, Ning; Tsang, Derek S; Taylor, Michael D; Bouffet, Eric; Nathan, Paul C; Ramaswamy, Vijay
Abstract: BACKGROUND: Most medulloblastoma survivors suffer from late treatment-related sequelae. There are no population-based studies examining such late effects in a dedicated cohort of medulloblastoma survivors. METHODS: Using a provincial pediatric cancer registry, all 5+ year medulloblastoma survivors diagnosed between 1987-2015 in Ontario, Canada were identified and matched to cancer-free population controls based on age, sex, and geographical location. Cases were followed from the index date (five years from latest of diagnosis, or relapse or subsequent malignancy prior to age 18 years) until December 31, 2020 or censorship (death, or relapse or new cancer after age 18 years). Clinical data were linked to administrative health databases to estimate cumulative incidences and cause-specific hazard ratios (HR) of mortality, hospitalizations, strokes, hearing loss requiring a hearing aid, and receipt of homecare services between cohorts, accounting for matching and competing risks. RESULTS: We identified 230 cases [65.7% female; median diagnostic age: 7y, interquartile range (IQR) 4-10; median attained age: 24y, IQR 18-31] and 1150 controls. One hundred eighty-seven (81.3%) received craniospinal irradiation. Ten-year survival probability after index was 92.4% in cases and 99.4% in controls (HR 21.5, 95% CI 9.8-54.0). Cases were at higher risk for hospitalizations (HR 3.4, 95% CI 2.7-4.3), stroke (HR 45.6, 95% CI 12.8-289.8), hearing loss (HR 96.3, 95% CI 39.7-317.3), and requiring homecare services (HR 7.9, 95% CI 5.8-10.9). By 10 years after index, 4.8% (95% CI 2.2-9.0) of survivors had experienced a stroke compared to 0.1% (95% CI 0.01-0.7) of controls. CONCLUSIONS: Survivors of childhood medulloblastoma experienced an increased risk of mortality and serious morbidity compared to population controls. Consideration for mitigation strategies or early interventions in preventing neurovascular sequelae and hearing loss is warranted, as are dedicated supports for survivors.